A study on lorry owners acceptance towards the implementation of the toll system at the North Klang Straits bypass / Zainul Hassan …[et al.] - Hassan, Zainul; Said, Munir; Mohamad, Mohd Bakry; Zainal, Zakiah; Mohamed Zain, Hazlinda (1985)
Roads are vital for the development and growth of a country. However, due to the high cost of construction, repair and maintenance of road in recent years, the government decided to introduce a toll system in newly built highways. Presently, the toll system are introduced at the Slim River Highway, Kuala Lumpur - Seremban Highway, Tambak Johor causeway and the North Klang Straits Bypass. The government also hopes to introduce the toll system at Bukit Kayu Hitam Highway, Senai - Johore Bahru, the Penang Bridge and the Kuala Lumpur - Karak 'Highway.